Q. 1 L4.7( 9 Votes )

# Find the errors and correct the following mathematical sentences

Substitute x = – 3 in

(c) x^{2} + 5x = (–3)^{2} + 5 (–3) + 6 = – 9 – 15 = –24

Answer :

If LHS is

x^{2} + 5x

Then RHS would be

⇒ x^{2} + 5x

Putting x = (-3)

= (–3)^{2} + 5 (–3)

= 9 + (-15)

= -6

The error is ( + 9) instead of (-9) and end results to (-6) instead of (-24)

Hence putting x = (-3) in x^{2} + 5x results to (-6)

Rate this question :

Find the errors and correct the following mathematical sentences

(3x)^{2} + 4x + 7 = 3x^{2} + 4x + 7

Find the errors and correct the following mathematical sentences

(2a + 3)^{2} = 2a^{2} + 6a + 9

Find the errors and correct the following mathematical sentences

(2x)^{2} + 5x = 4x + 5x = 9x

Find the errors and correct the following mathematical sentences

Substitute x = – 3 in

(b) x^{2}– 5x + 6 = (–3)^{2} –5 (–3) + 6 = 9 – 15 + 6 = 0

Find the errors and correct the following mathematical sentences

Substitute x = – 3 in

(c) x^{2} + 5x = (–3)^{2} + 5 (–3) + 6 = – 9 – 15 = –24

Find the errors and correct the following mathematical sentences

(x – 4)^{2} = x^{2} – 16